Dynamics of Candidates for Independent Regent/ Deputy Regent of Batu Bara Regency from the Siyasah Fiqh Perspective - Dasopang, Andre Frandika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The General Election of Regional Heads in Batu Bara Regency after this district was split from Asahan Regency in 2007 has experienced 3 (three) Regent/Deputy Regent election periods, namely in 2008, 2013, and 2018. Regional Head Elections in Batu Bara Regency There is a dynamic condition of the independent nomination of Regent/Deputy Regent in the three regional head elections that were held. There is a decrease in the number of Regent/Deputy Regent Candidate pairs in each regional head general election that is held, there is a decrease in the number of Regent/Deputy Regent Candidate pairs from the independent route. Candidate pairs for Regent/Deputy Regent who used the independent route in 2008 were 4 (four) pairs (57.14%) out of a total of 7 (seven) candidate pairs, this means that there were more than candidate pairs who used the party route. In 2013, there was another decline in the number of independent candidate pairs for Regent/Deputy Regent by 2 (two) pairs (33.33%) out of a total of 6 (six) candidate pairs. A significant decline occurred in the Batu Bara Regency regional head election in 2018, namely only 25.00% or 1 candidate pair out of a total of 4 (four) Regent/Deputy Regent Candidate pairs who registered with the Batu Bara Regency General Election Commission (KPU). Seeing the phenomenon of the decline in the number of Regent/Deputy Regent Candidate pairs in Batu Bara Regency on the independent route, it is necessary to analyze it, to find out what is causing the lack of interest in Regent/Deputy Regent Candidate pairs to nominate themselves through the independent route, and preferring the party route. even though the rules regarding the permissibility of independent/individual registration of Regent/Deputy Regent Candidate pairs are still permitted in the existing general election laws and regulations in Indonesia, as contained in Article 1 paragraph (4) of Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning the Stipulation of Government Regulations instead of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors into Law.